A Systematic Approach for the Reliability Evaluation of Electric Connector. (6th May 2021) - Wang, Ruoyu; Xu, Liangjun; Zhou, Yilin
Abstract : Under the trend of high density and miniaturization, the current that the connector transmits per unit volume is getting higher and higher, which makes the reliability design of the connector more challenging. Under the pressure of high performance and low cost requirements, the design has to be more accurate and more efficient. Thus, in the design process, a systematic approach for reliability evaluation is required. However, there is no valid enough approach that is integrated, well-organized, and quantitative. In this article, a systematic approach for the reliability evaluation of connector was proposed, and by applying it on a typical object named a blade-spring connector, the validity of this approach was verified. After the framework of this approach has been established, the methods and models needed were provided, including the method to build up material selection criterion and the assessment models of stress relaxation, thermal diffusion, and sliding wear, respectively. Then, the feasibility of a newly developed copper alloy on the connector and the reliability behaviors of this connector were determined through this approach. The unsatisfactory aspects of reliability were pointed out and some possible redesign choices were provided. Results and discussion revealed that the proposed approach is a helpful tool for designing electric connectors, especially on the reliability design.